Exploring adolescents’ digital information-seeking patterns and religious behavior - Purwaningtyas, Franindya; Dalimunte, Muhammad; Dewi, Shinta (Universitas Padjadjaran, 2024)
Generation Z adolescents' religious information-seeking behavior has undergone significant transformations in understanding and studying the patterns of searching, processing, and using religious information. Research gaps exist in local cultural variations on transforming Generazion Z adolescents' religious information-seeking behavior in the digital era, which also occurs in information access patterns, social media platform preferences, and responses to religious content. This study focused on information access using the Ellis Model to analyze the behavior of information search stages: browsing, chaining, filtering, monitoring, and understanding adolescents' religious preferences. This study used a qualitative approach with a case study method involving Rohis activists from six high schools in three cities, Medan, Yogyakarta, and Makassar, as research samples. Data were collected through observation and FGD. Study results showed that Generation Z accessed religious information digitally through social media due to its accessibility and interactivity. However, they still referred to local and popular religious figures to clarify and validate religious information. Social media played an important role in shaping religious views despite the challenges of spreading misinformation and disinformation. Their information-seeking behavior reflected a combination of digital exploration and conventional references; adolescents actively utilized, created, and shared religious information. The Ellis Model's relevance in understanding information-seeking behavior in the digital era and cultural variations contributes to information behavior study by highlighting the dynamics of technology use in meeting the younger generation's spiritual needs. Practical implications include recommendations for improving digital literacy through technology-based education and partnerships with religious authorities to provide credible and moderate content.